2014
DOI: 10.1007/s00128-014-1324-4
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Concentrations in Two Populations of Mopane Worms (Imbrasia belina) in the Kruger National Park Pose a Potential Human Health Risk

Abstract: Metal concentrations in Mopane worms from Phalaborwa and Shangoni sites in the Kruger National Park were determined. Metal concentrations were evaluated by inductively coupled plasma optical emission spectroscopy (ICP-OES) and ICP-MS spectrometry after microwave digestion. The results indicate a substantial bioaccumulation of metals in Mopane worms. In Phalaborwa Cd concentrations were 15 times and Cu two times higher than the EU and UK recommended legal limits for human consumption, Zn levels were tolerable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The concentration of toxic metals in the plant leaves on which mopane worms were extracted from was compared to those obtained from mopane worms, and substantial bioaccumulation of Cd, Cu, Co, and Mn in mopane worms was reported. The samples were collected from the Kruger National Park in the Limpopo Province of South Africa, and the highest concentrations of Cd, Cu, Co, and Mn were 4.02, 47.73, 4.52, and 3.37 μ g g −1 , respectively, and all these values were above the recommended guidelines by the European Union [ 49 ]. However, in the current study, the concentrations of metals were well below detection limits and we can conclude that the consumption of mopane worms remains safe from potential metal contamination, while concentrations of As in sweet corn should be of serious concern.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of toxic metals in the plant leaves on which mopane worms were extracted from was compared to those obtained from mopane worms, and substantial bioaccumulation of Cd, Cu, Co, and Mn in mopane worms was reported. The samples were collected from the Kruger National Park in the Limpopo Province of South Africa, and the highest concentrations of Cd, Cu, Co, and Mn were 4.02, 47.73, 4.52, and 3.37 μ g g −1 , respectively, and all these values were above the recommended guidelines by the European Union [ 49 ]. However, in the current study, the concentrations of metals were well below detection limits and we can conclude that the consumption of mopane worms remains safe from potential metal contamination, while concentrations of As in sweet corn should be of serious concern.…”
Section: Resultsmentioning
confidence: 99%
“…Greenfield, Akala and van der Bank detected high concentrations of heavy metals in Mopane worms (Imbrasia belina) taken from two sites at a South African national park: cadmium, copper and zinc concentrations were respectively 15-21, 2-2.5 and 0.4 times higher than the recommended legal levels in the United Kingdom and European Union [137]. The concentration of manganese in I. belina was 20-67 times higher than the food safety standard set by the United States Food and Drug Administration [137]. Others found that contaminated feeds led to the accumulation of cadmium, lead or arsenic in soldier fly larvae (Hermetia illucens) and yellow mealworms (T. molitor) [123,138], with one study also suggesting that the accumulation rate was dependent on the insect species and type of metal present [138].…”
Section: Food Safety Risks Of Edible Insects: Bacteria Mycotoxins Par...mentioning
confidence: 97%
“…Vijver et al reported that cadmium, copper, lead and zinc present in soils (naturally or artificially contaminated) were retained in the body of T. molitor, with the extent of accumulation depending on the type of soil and metal [136]. Greenfield, Akala and van der Bank detected high concentrations of heavy metals in Mopane worms (Imbrasia belina) taken from two sites at a South African national park: cadmium, copper and zinc concentrations were respectively 15-21, 2-2.5 and 0.4 times higher than the recommended legal levels in the United Kingdom and European Union [137]. The concentration of manganese in I. belina was 20-67 times higher than the food safety standard set by the United States Food and Drug Administration [137].…”
Section: Food Safety Risks Of Edible Insects: Bacteria Mycotoxins Par...mentioning
confidence: 98%
“…The data showed that the amount of manganese in wild termites was 50–100 times higher than the concentration detected in other insects. From a safety point of view, wild insects may have excessive levels of heavy metals due to the complex and harsh growing environment [ 247 ]. This is not good for insects as a food source.…”
Section: Factors To Consider In the Consumption Of Edible Insectsmentioning
confidence: 99%